2016
DOI: 10.1126/sciadv.1501778
|View full text |Cite
|
Sign up to set email alerts
|

Microscale spatial heterogeneity of protein structural transitions in fibrin matrices

Abstract: Following an injury, a blood clot must form at the wound site to stop bleeding before skin repair can occur. Blood clots must satisfy a unique set of material requirements; they need to be sufficiently strong to resist pressure from the arterial blood flow but must be highly flexible to support large strains associated with tissue movement around the wound. These combined properties are enabled by a fibrous matrix consisting of the protein fibrin. Fibrin hydrogels can support large macroscopic strains owing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 52 publications
(100 reference statements)
4
51
0
Order By: Relevance
“…The molecular properties of fibrin, specifically the confirmation, or molecular structure, of fibrin monomers within the fibers, and their relation to fibrin biology and biochemistry, have remained largely absent from the fibrin structure-function literature. This is despite evidence by many groups [18][19][20], including us [7], showing that fibrin molecular structure changes from a dominant α-helix to a dominant β-sheet motif and that molecular distances in fibrin fibers shrink with increasing deformation [20,21].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The molecular properties of fibrin, specifically the confirmation, or molecular structure, of fibrin monomers within the fibers, and their relation to fibrin biology and biochemistry, have remained largely absent from the fibrin structure-function literature. This is despite evidence by many groups [18][19][20], including us [7], showing that fibrin molecular structure changes from a dominant α-helix to a dominant β-sheet motif and that molecular distances in fibrin fibers shrink with increasing deformation [20,21].…”
Section: Introductionmentioning
confidence: 81%
“…These biomechanical properties of fibrin depend on its hierarchical structure, building up from the molecular to the fiber level [4]. Several studies have concentrated on understanding and evaluating structural changes in fibrin under mechanical deformation and how those changes correlate to clot stability [3][4][5][6][7]. In addition, Bucay et al and Li et al showed that stretching single fibrin fibers affected plasmin-mediated fibrinolysis, albeit with opposite effects.…”
Section: Introductionmentioning
confidence: 99%
“…This is comparable in order of magnitude to the shift reported in a recent SAXS study of pre-aligned plasma clots under uniaxial strain, where the shift was 5% when the tensile strain reached 40% (at which point the peak disappeared) 60 . Several studies showed direct evidence of forced unfolding of fibrin monomers within fibrin gels subject to large shear or tensile loads, using wide-angle X-ray scattering 74 or vibrational spectroscopy 41,42 . Indeed, due to axial and transverse crosslinking of the protofibrils, it is likely that stretching of the αC-regions is somehow coupled to protofibril elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a few studies have started to address this challenge by performing in situ measurements of structural changes in mechanically deformed fibrin networks. Vibrational spectroscopy has revealed evidence of monomer unfolding (α-helical to β-sheet conversion) in stretched fibrin networks 41,42 , Small Angle X-ray Scattering (SAXS) has provided evidence of monomer unfolding based on changes in the axial packing periodicity of fibers within stretched clots 39 visible through a shift of the Bragg peak 26 , and confocal imaging has shown that fibers reorient and can irreversibly lengthen upon repeated straining 43 . Altogether, there is convincing evidence that molecular unfolding occurs at macroscopic tensile strains above 100%, but it remains unclear to what extent other mechanisms (in particular fiber reorientation and stretching of the unstructured αC-regions) also contribute to the macroscopic elasticity, and how this depends on strain 44 .…”
Section: Figurementioning
confidence: 99%
“…A label-free method like CARS microscopy, 24,25 which generates chemical contrast based on inherent molecular vibrations, here the CH 3 vibration of proteins, has the capability to provide information about the natural state of the proteins in the hydrogel at physiological conditions. 26,27 Being an optical technique, CARS microscopy enables investigations of soft materials even under hydrated conditions and requires no physical contact, which is challenging for most AFM probes. Furthermore, it is easily combined with two-photon excited fluorescence (TPEF) microscopy, allowing for simultaneous observations of living cells and their dynamic interaction with the hydrogel scaffolds at short integration times.…”
Section: Introductionmentioning
confidence: 99%